Demystifying consumerism: towards tackling the problem of quackery in Nigeria (2009)
Marketplaces are flooded with goods and services from which consumers must choose. Consumers are in this way faced with challenges of choosing goods and services that will satisfy their wants and have positive impact on their health. Studies have shown that many of the goods available in marketplaces are fake, expired or contaminated. Quacks render ineffective health services. Information provided about the goods and services are deceptive and inadequate. This paper examines problems of quackery and consumerism and the importance of consumerism. It also explains rights of consumer and corresponding laws as well as consumer health protection agencies and consumer health education. The paper concludes that consumer’s rights could be protected through legal means. The paper recommends the integration of consumerism into school curricula and massive public enlightenment on the activities of quacks in Nigeria.